Clinical and paraclinical criteria for prognosis of the hemorrhagic transformation of hemispheric cerebral infarction and its influence on the outcome of the acute period of the disease - O. A. Kozyolkin; A. A. Kuznietsov; N. I. Voevodin (Zaporožskij Medicinskij Žurnal)
Standardizated criteria for predicting hemorrhagic transformation of cerebral infarction are currently absent.